Enhancing the role of educational institutions in developing scientific and educational competencies. Sustainable strategies to face the challenges of contemporary society. - Naimah, Assistant Professor Dr. Mohammed Wajd Al-Naimah; Ali, Dr. Salwa Mohammed Ali (Sulaimani Journal for Humanities, 2026)
Amid the rapid transformations in contemporary society, including economic, social, and technological challenges, educational institutions face a significant responsibility in developing scientific and pedagogical competencies capable of keeping pace with these changes. This study aims to explore the role of educational institutions in enhancing these competencies and proposes sustainable strategies to strengthen their ability to address emerging challenges. The focus will be on analyzing how these competencies are developed through higher education and how educational institutions respond to the evolving needs of society. Additionally, the study will present sustainable solutions based on partnerships between education and the labor market.
Keywords: Educational institutions; competency development; sustainable strategies; skillsbased education; digital transformation